On density and flow of energy in nonrelativistic quantum mechanics - Chaus , N. N. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A number of mathematical consequences of the Schroedinger equation iψ = H_ψ are given and interpreted as local energy and momentum conservation laws. Several Hamiltonians are treated.